Synthesis of Allylic and Propargylic Trifluoromethyl Thioethers by Copper(I)‐Catalyzed Trifluoromethylthiolation of Allylic Bromides and Propargylic Chlorides. Issue 23 (10th July 2014) - Rong, Mingguang; Li, Dongzhe; Huang, Ronglu; Huang, Yangjie; Han, Xiaoyan; Weng, Zhiqiang
Abstract: An efficient method is reported for the copper(I)‐catalyzed trifluoromethylthiolation of allylic bromides by using elemental sulfur and CF3 SiMe3 . This rate of this transformation was significantly accelerated in the presence of 18‐crown‐6, and the reaction afforded the desired products in moderate to excellent yields with high stereo‐ and regioselectivity. This method can tolerate a number of functional groups and provides facile access to a variety of allylic trifluoromethyl thioethers. The copper(I)‐catalyzed trifluoromethylthiolation of propargylic chlorides was also investigated. A plausible mechanism that involves an allylcopper(III) intermediate is proposed. Abstract : We report a copper(I)‐catalyzed trifluoromethylthiolation of allylic bromides and propargylic chlorides by using elemental sulfur and CF3 SiMe3 to synthesize allylic and propargylic trifluoromethyl thioethers. This method, which can tolerate a number of functional groups, afforded a variety of desired products in moderate to excellent yields.